Algeria : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
The strong hydrocarbon export performance has allowed Algeria to strengthen its external position and record a budget surplus. Executive Directors commend the government for the broad improvement in macroeconomic indicators. The government has eased the fiscal stance, and this strategy has succeeded in boosting short-term growth. The surge in credit to the economy is a concern. Algeria should reinvigorate its structural and institutional reform efforts to put the economy on a sustainable path of higher growth, lower unemployment, improved social conditions, and reduced poverty.